2017
DOI: 10.1371/journal.pgen.1007073
|View full text |Cite
|
Sign up to set email alerts
|

RhoGEF9 splice isoforms influence neuronal maturation and synapse formation downstream of α2 GABAA receptors

Abstract: In developing brain neuronal migration, dendrite outgrowth and dendritic spine outgrowth are controlled by Cdc42, a small GTPase of the Rho family, and its activators. Cdc42 function in promoting actin polymerization is crucial for glutamatergic synapse regulation. Here, we focus on GABAergic synapse-specific activator of Cdc42, collybistin (CB) and examine functional differences between its splice isoforms CB1 and CB2. We report that CB1 and CB2 differentially regulate GABAergic synapse formation in vitro alo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Of these, only CbII and CbIII are expressed in adult neurons (Harvey et al, 2004). A previous report indicates that CbI and CbII differentially regulate GABAergic synapse formation during development, and that the functional specialization of these Cb isoforms arises from their differential protein half-life, which is controlled through ubiquitin conjugation at the unique CbI C-terminus (de Groot et al, 2017). Instead, CbII and CbIII do not differ with regard to postsynaptic targeting and their ability to induce gephyrin clustering upon overexpression in neurons (Chiou et al, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…Of these, only CbII and CbIII are expressed in adult neurons (Harvey et al, 2004). A previous report indicates that CbI and CbII differentially regulate GABAergic synapse formation during development, and that the functional specialization of these Cb isoforms arises from their differential protein half-life, which is controlled through ubiquitin conjugation at the unique CbI C-terminus (de Groot et al, 2017). Instead, CbII and CbIII do not differ with regard to postsynaptic targeting and their ability to induce gephyrin clustering upon overexpression in neurons (Chiou et al, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…While the mechanisms of ictogenesis remain unclear, it is generally accepted that inhibitory control of excitation is a contributing factor (Fritschy, 2008). In addition, AIS dysfunction and mutations in the human CB gene ARHGEF9 are both linked to epileptic disorders in humans (Buffington and Rasband, 2011;de Groot et al, 2017;Kalscheuer et al, 2009;Shimojima et al, 2011;Wimmer et al, 2010). The Gabra1-2 mutation enhances inhibitory neurotransmission, resulting in a reduction in the susceptibility of Gabra1-2 mice to kainate-induced seizures.…”
Section: Discussionmentioning
confidence: 99%
“…For collybistin, three major C-terminal isoforms have been described (CB1-3, Harvey et al, 2004). While distinct CB2 isoforms regulate translocation of gephyrin to the cell surface and formation and maintenance of gephyrin clusters at GABAergic sites (Tyagarajan et al, 2011), the CB1 isoform has been shown to selectively facilitate gephyrin clustering at distal portions of immature dendrites (de Groot et al, 2017). Alternative splicing in both the CB1 and CB2 isoforms have been observed (Harvey et al, 2004; de Groot et al, 2017).…”
Section: Gene Isoforms In Gabaergic Signalingmentioning
confidence: 99%